Toward sustainability or efficiency: The case of smallholder coffee farmers in Vietnam - Hung Anh Nguyen; Wolfgang Bokelmann; Do Thi Nga; Nguyen Van Minh (Economies, 2019)
This study attempts to uncover the truth behind an increasing number of smallholder farmers participating in sustainable coffee farming in Vietnam. Using stochastic frontier and cost-benefit analysis, a sample of 316 smallholder farmers in Dak Lak was chosen to analyze the economic impacts of sustainable and conventional coffee farming on farmers' welfare. In addition, we conducted field observation and key informant interviews to describe several farming practices. The results highlight the fact that farmers' decisions to participate in sustainable coffee farming are mainly driven by economic benefits. Sustainable farming is more cost-effective and profitable than conventional farming, despite the insignificant difference in production efficiency. Improvement of education, farming knowledge, and collective actions could mitigate negative effects of small-scale production for sustainable coffee farmers. Pesticide management, shade coffee encouragement, and reduction of excessive fertilization, over-irrigation, and unproductive coffee varieties are recommended for sustainable development of the sector.
Keywords: 330; sustainable; conventional; smallholder farmer; technical efficiency; stochastic frontier